Aplikasi TikTok dengan Model PBLA untuk Meningkatkan Kemampuan Argumentasi Peserta Didik pada Konsep Pengukuran Fisika - Prastiwi, Ayu Nita; Fatmaryanti, Siska Desy; Akhdinirwanto, Raden Wakhid (PendIPA Journal of Science Education, 2024)
This study aims to develop learning media by utilizing the TikTok application with the PBLA model on the topic of measurement and to determine the enhancement of participants' argumentation skills. This study is a Research and Development (R&D) study employing the ADDIE development procedure (Analyze, Design, Development, Implementation, and Evaluation). The research subjects were 36 students from class X-E of MAN Purworejo in the academic year 2023/2024. The research instruments used were validation sheets, participant response questionnaires, observation sheets, pretest-posttest questions, and learning implementation sheets. The data analysis results show that the physics instructional video media utilizing the TikTok application with the PBLA model meets the "valid" criteria, with material expert validation scoring 3.45, equivalent to 86.30%, categorized as "good," and media expert validation scoring 3.58, equivalent to 89.58%, categorized as "very good." The developed physics instructional video media using the TikTok application with the PBLA model received a score of 85.5% with the predicate "very good" from participant response testing. Meanwhile, the observation data on learning implementation achieved a Percentage Agreement (PA) score of 99% with the predicate "reliable," meeting the "practical" criteria. Utilizing the TikTok application with the PBLA model is effective according to trial results using a paired sample t-test, which produced a calculated t-value of 0.000 < 0.05, indicating an improvement in argumentation skills after using physics learning media with the TikTok application. Thus, the developed physics learning media is considered "effective" for improving students' argumentation skills based on pretest and posttest scores with a normalized gain of 0.71, which falls into the "high" category.